2012
DOI: 10.1139/h2012-013
|View full text |Cite
|
Sign up to set email alerts
|

Composite versus single transportable carbohydrate solution enhances race and laboratory cycling performance

Abstract: When ingested at high rates (1.8-2.4 g·min(-1)) in concentrated solutions, carbohydrates absorbed by multiple (e.g., fructose and glucose) vs. single intestinal transporters can increase exogenous carbohydrate oxidation and endurance performance, but their effect when ingested at lower, more realistic, rates during intermittent high-intensity endurance competition and trials is unknown. Trained cyclists participated in two independent randomized crossover investigations comprising mountain-bike races (average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 36 publications
9
64
1
2
Order By: Relevance
“…In contrast to previous research, [7,8,10,15] no improvement in performance was recorded during a 40 km laboratory time trial between the GP and the mixed drinks (p=0.289). Triplett et al [8] showed an 8.1% improvement in time trial performance when participants ingested approximately 144 g (or 2.4 g/min) of drinks containing either GP only, or a GP and fructose (1:1 ratio) mixed drink.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous research, [7,8,10,15] no improvement in performance was recorded during a 40 km laboratory time trial between the GP and the mixed drinks (p=0.289). Triplett et al [8] showed an 8.1% improvement in time trial performance when participants ingested approximately 144 g (or 2.4 g/min) of drinks containing either GP only, or a GP and fructose (1:1 ratio) mixed drink.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, O'Brien and Rowlands [9] have shown that higher rates of exogenous carbohydrate oxidation with a multiple carbohydrate drink result in an improvement in performance over and above that of when an isocaloric single carbohydrate with concomitant lower oxidation rate is ingested. Furthermore, the studies by Rowlands et al [10] and Currell and Jeukendrup [7] measured endogenous a carbohydrate oxidation rates in addition to performance parameters, however, exogenous oxidation rates were not measured and it was assumed that the oxidation rate of the multiple CHO drink ingested was higher.The present study aimed to determine if a superior performance is attained when a multiple carbohydrate drink is ingested. Specifically, time trial performances were compared in a single group of highly trained cyclists to determine whether a multiple carbohydrate drink (glucose: fructose in a 2:1 ratio) confers a performance advantage over that of a single carbohydrate drink (glucose-polymer only), the physiological parameters of lactate, insulin and glucose concentrations, substrate oxidation (total, endogenous and exogenous) and respiratory exchange, will be measured, which may explain the underlying mechanisms that relate to any performance differences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated the superiority of multiple versus single transportable carbohydrates for prolonged endurance exercise performance when carbohydrate is consumed in large quantities (Currell & Jeukendrup, 2008;Rowlands et al, 2012;Triplett et al, 2010). Undoubtedly, some of the benefit of ingesting multiple transportable carbohydrates can be attributed to increased exogenous fuel provision during exercise as compared with single transportable carbohydrates.…”
Section: Sucrose Consumption During Exercise and Performancementioning
confidence: 99%
“…Undoubtedly, some of the benefit of ingesting multiple transportable carbohydrates can be attributed to increased exogenous fuel provision during exercise as compared with single transportable carbohydrates. In addition, improved gastro-intestinal comfort with multiple transportable carbohydrates has been identified as a possible mediating mechanism in explaining the endurance performance benefits of multiple over single transportable carbohydrates (Rowlands et al, 2012). This is perhaps not surprising given the use of highly concentrated-hypertonic glucose-only control solutions which can demonstrably induce severe gastro-intestinal distress during prolonged exercise (Triplett et al, 2010).…”
Section: Sucrose Consumption During Exercise and Performancementioning
confidence: 99%